Budaya Lokal dan Film: Respon Penonton terhadap Film Yowis Ben Karya Bayu Skak - Nathania Chelsea Mineri; Edi Dwi Riyanto (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
This study examines the audience’s response to the representation of local culture, especially the city of Malang, which are shown in the movie Yowis Ben. The purpose of this study is to find out the responses given by the audience to the local Malang’s culture in the movie. This study used a qualitative descriptive method with Stuart Hall’s reception analysis approach. The results of the study show that cultural representation of the use of Javanese language with the representation of local culinary of pecel is dominated by a dominant-hegemonic position where the audience fully accepts the message conveyed, meanwhile using local swear words known as pisuhan is dominated by negotiated position where the audience can accept the dominant code but reject it by making a selection. Researcher viewed that this movie is a good media in introducing a local culture of Malang to a wider audiences.